Pengembangan Bakat Dan Minat Mahasiswa Dalam Bidang Olahraga Melalui Pengenalan Dan Pendampingan Olahraga Panahan - Bramantha, Heldie; Setiawan, Gustilas Ade (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2022)
Archery is a sport that is recommended in Islam and sunnah by the prophet Muhammad Shallalahu 'alaihi wasallam. This sport has long been known in Indonesia, by carrying out archery activities each individual is able to train strength, endurance, focus, hand and eye coordination, balance, increase hand and finger flexibility, increase patience and build self-confidence. The problem that occurs in the community in the city of Situbondo, especially for students at the Abdurachman Saleh University Situbondo, is that Archery is still not well known and is also still less attractive to the public because archery has not yet become a